1-(4-Antipyrine)-3-(2,4,6-tribromophenyl)triazene and its Chromogenic Reaction with Cadmium - Zhang1, Xue-Hong; Chen2, Wen-Bin (Asian Journal of Chemistry, 2013)
The chromogenic reagent 1-(4-antipyrine)-3-(2,4,6-tribrominephenyl)triazene (ATTBPT) was synthesized and its colour reaction with cadmium has been investigated in the presence of the microemulsion OP. In the Na2B4O7-NaOH medium of pH 10.5, the reagent reacts with Cd(II) to form an orange-yellow complex with a molar ratio of 2:1. The complex has a maximum absorption at 460 nm. The apparent molar absorptivity of the complex was 1.7 × 104 L mol-1 cm-1. Beer’s law was obeyed in the range of 0-12 μg/10 mL for cadmium. The method has been applied to the direct determination of cadmium in real samples with satisfactory results.